FORMALISASI HUKUM ISLAM DALAM BENTUK PERATURAN DAERAH: ANALISIS PERATURAN DAERAH SYARIAH DI BULUKUMBA - Abdul Syatar; Juliana Juliana; Zehratul Eitriya; Rifaldi Rifaldi; Winanda Winanda; Alfajri Anugrah; Angelina Atika Putri (Fakultas Syariah Institut Agama Islam Negeri Palu, 2021)
This article aims to examine the formalization of Islamic law in the form of a Sharia Regional Regulation (Perda) in Bulukumba. The approach in this research is juridical-normative. This approach is used to understand the phenomenon of the formalization of Islamic law in the Bulukumba area. The results show that the formalization and application of sharia regulations in Bulukumba is running quite well, this is based on the development of public understanding and compliance with the Perda. On the other hand, these sharia-based regulations sometimes run less effectively. This is because there are still many Bulukumba people who do not know, let alone understand the Sharia Regional Regulations well.